2015
DOI: 10.1186/s13075-015-0840-x
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage stem/progenitor cells are activated in osteoarthritis via interleukin-1β/nerve growth factor signaling

Abstract: IntroductionInterleukin-1β (IL-1β) and nerve growth factor (NGF) are key regulators in the pathogenesis of inflammatory arthritis; specifically, IL-1β is involved in tissue degeneration and NGF is involved in joint pain. However, the cellular and molecular interactions between IL-1β and NGF in articular cartilage are not known. Cartilage stem/progenitor cells (CSPCs) have recently been identified in osteoarthritic (OA) cartilage on the basis of their migratory properties. Here we hypothesize that IL-1β/NGF sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 40 publications
5
40
0
Order By: Relevance
“…Nerve growth is observed in human OA joints, and NGF is known to be involved in neuropathic pain transmission (26,27); however, it is not clear whether NGF plays a role in joint degeneration. Our group has recently found that expression of NGF and NGFRs in OA cartilage is associated with a subpopulation of tissue-specific stem and progenitor cells in vivo and can be regulated by the OA mediator IL-1b (18). The in vitro findings reported here provide further evidence supporting the functional involvement of NGF-NGFR signaling in OA pathogenesis, specifically suggesting a role in hACs homeostasis and pathologic calcification.…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations
“…Nerve growth is observed in human OA joints, and NGF is known to be involved in neuropathic pain transmission (26,27); however, it is not clear whether NGF plays a role in joint degeneration. Our group has recently found that expression of NGF and NGFRs in OA cartilage is associated with a subpopulation of tissue-specific stem and progenitor cells in vivo and can be regulated by the OA mediator IL-1b (18). The in vitro findings reported here provide further evidence supporting the functional involvement of NGF-NGFR signaling in OA pathogenesis, specifically suggesting a role in hACs homeostasis and pathologic calcification.…”
Section: Discussionsupporting
confidence: 72%
“…Other groups and our recent findings strongly implicated the involvement of NGF-and NGF receptor (NGFR)mediated signaling in OA pathogenesis in cartilage, evidenced by the active presence of the high-affinity NGFR tropomyosin receptor kinase A (TrkA) and low-affinity NGFRs [P75 neurotrophin receptor (P75NTR), CD271] in human OA cartilage (16,17) and the elevation of NGF expression in cultured chondrocytes induced by the OA mediator and proinflammatory cytokine IL-1b (18). In addition, a population of NGF-responsive migratory progenitor cells has been identified in OA cartilage (18,19). However, the exact function of NGF and NGFR in articular cartilage biology and OA pathogenesis remains to be clarified.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…The chondrogenic potential of chondrocytes has been reported to have a negative correlation with cell migration ability in a two‐dimensional cell migration assay (O'Connell et al ., ). Others using articular chondrocytes have also found the important role of cell migration in cartilage catabolism (Pereira et al ., ; Jiang et al ., ). Our results demonstrated that the weaker chondrogenic phenotype in P 1 healthy chondrocyte was accompanied with its stronger migration ability and increased expression of stemness‐related genes, which further confirmed the faster dedifferentiation potential in healthy ear chondrocytes than in microtia.…”
Section: Discussionmentioning
confidence: 97%